Comparing the effect of different treatments for breaking seeds dormancy of Brachychiton populneus trees cultivated in Al-Jabal Al-Akhdar region-Libya - salih, Sami mohammed; Abdulrraziq, Ahmed amrajaa; Mohammed, Sameer Salih (Al-Mukhtar Journal of Sciences, 2019)
Brachychiton populneus is an ornamental tree that adapts ecologically and newly-introduced to Al-jabal Al-akhdar region - Libya. The study aimed to investigate the effect of several different breaking-dormancy treatments for the seeds of Brachychiton populneus Including the treatments of soaking in concentrated sulphuric acid for periods of (10, 20 and 30) minutes, the scarification (mechanical scarification, scarification with soaking in gibberellin 100ppm, scarification with soaking in Indole-3-butyric acid 100ppm), soaking in hot water for periods of (20, 30 and 40) minutes, soaking in gibberellin concentrations 100, 200, and 300pmm, and finally soaking in Indole-3-butyric acid concentrations 100, 200, and 300pmm. Results showed the superiority of treatment of soaking in concentrated sulphuric acid for 30 minutes on all treatments with a germination percentage of 92% and the lowest average germination time of 3.56 days followed by different scarification treatments, while plant hormon treatments (GA3, IBA) were ineffective in breaking dormancy and improving germination. The study concluded that the best method for breaking dormancy caused by the hardness of Brachychiton populneus seeds was the treatment of concentrated sulphuric acid for 30 minutes.